1995
DOI: 10.1126/science.7652575
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for Rho, Rac, and Cdc42 GTPases in Cell Cycle Progression Through G 1

Abstract: Members of the Rho family of small guanosine triphosphatases (GTPases) regulate the organization of the actin cytoskeleton; Rho controls the assembly of actin stress fibers and focal adhesion complexes, Rac regulates actin filament accumulation at the plasma membrane to produce lamellipodia and membrane ruffles, and Cdc42 stimulates the formation of filopodia. When microinjected into quiescent fibroblasts, Rho, Rac, and Cdc42 stimulated cell cycle progression through G1 and subsequent DNA synthesis. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
897
6
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,120 publications
(945 citation statements)
references
References 27 publications
34
897
6
8
Order By: Relevance
“…Activation of ER by Brx was not a ected by dominant negative mutants of Rac-1, RhoA, or by C3 transferase expression; in agreement with studies documenting distinct signal transduction pathways for these Rho family members (Coso et al, 1995;Minden et al, 1995;Olson et al, 1995). Rac and Cdc42Hs, originally reported to regulate actin cytoskeletal organization, were more recently shown to interact with proteins involved in mitogenesis and to a ect nuclear signaling through activation of transcription by serum response factor (SRF) (Hill et al, 1995), JNK (Coso et al, 1995;Minden et al, 1995;Olson et al, 1995), and pp70 S6K (Chou and Blenis, 1996). The data presented here expand the set of proteins in¯uenced by Cdc42 to include a liganddependent transcription factor, the estrogen receptor.…”
Section: Discussionsupporting
confidence: 87%
“…Activation of ER by Brx was not a ected by dominant negative mutants of Rac-1, RhoA, or by C3 transferase expression; in agreement with studies documenting distinct signal transduction pathways for these Rho family members (Coso et al, 1995;Minden et al, 1995;Olson et al, 1995). Rac and Cdc42Hs, originally reported to regulate actin cytoskeletal organization, were more recently shown to interact with proteins involved in mitogenesis and to a ect nuclear signaling through activation of transcription by serum response factor (SRF) (Hill et al, 1995), JNK (Coso et al, 1995;Minden et al, 1995;Olson et al, 1995), and pp70 S6K (Chou and Blenis, 1996). The data presented here expand the set of proteins in¯uenced by Cdc42 to include a liganddependent transcription factor, the estrogen receptor.…”
Section: Discussionsupporting
confidence: 87%
“…The myc-tagged dominantnegative Rac1 (N17) was a gift from Dr A Hall (SloanKettering Institute, New York, NY, USA) (Olson et al, 1995), and dominant-negative Cdc42 (N17) and RhoA (N19) (Olson et al, 1995) were obtained from UMR cDNA Resource Center (Rolla, MO, USA). The IL2R/E-cadherin membrane proximal chimera construct was provided by Dr C Gottardi (Northwestern University, Chicago, IL, USA) (Miranda et al, 2001).…”
Section: Constructs and Transfectionsmentioning
confidence: 99%
“…It appears that the signals from Ga 12/13 are translated into growth-promoting signals by the small GTPases Ras, Rac, and Rho. It has been reported that Ras, Rho, Rac, and CDC42 play an essential role in cell cycle progression from G1 to S phase (Aktas et al, 1997;Takuwa and Takuwa, 1997;Olson et al, 1995;Hirai et al, 1997). An additional role for Rac in progression from G2 to M phase has been also identi®ed (Moore et al, 1997).…”
Section: Ga 12/13 : the Gep Oncogenes?mentioning
confidence: 99%